The effectiveness of money laundering awareness education programs to combat money mule job acceptance among public university students in Malaysia - Mohanamerry, Vedamanikam (2025)
This study provides an in-depth analysis of a significant issue affecting the Malaysian higher education system: the recruitment of university students as money mules. This research is motivated by the alarming rise in financial crimes targeting vulnerable populations, particularly young adults, who unwittingly become accomplices in illicit money laundering schemes. In this study, a multidisciplinary approach is adopted, drawing upon insights from criminology, financial education, and cybersecurity to elucidate the complex factors influencing students' susceptibility to money mule recruitment. This research has three Research questions, three Research objectives and 3 hypotheses. By employing a quantitative research design, the investigation seeks to unravel the underlying mechanisms driving students' decisions to accept offers to facilitate illegal financial transactions. A quasi-experimental design was employed, with a sample of 1,018 students selected for this study. Through extensive data collection and analysis, the research examines the levels of awareness, understanding of money laundering mechanisms, and cognitive processes involved in rationalizing participation in illicit activities among higher education students. The results show that knowledge of money laundering (crime awareness), identification of criminal intentions, rational thinking and job acceptance have significant relationships. Central to this inquiry is the development and implementation of a novel knowledge-based rational thinking framework, designed to equip students with the critical thinking skills and ethical awareness necessary to resist the allure of illicit financial gains. The findings of this thesis contribute significant insights into the efficacy of educational interventions aimed at mitigating the risk of money mule recruitment among university students. By elucidating the socio-psychological factors underpinning students' vulnerability to financial exploitation, the study offers valuable implications for policymakers, educators, and law enforcement agencies tasked with combating financial crimes and safeguarding the integrity of the higher education system. Ultimately, this research endeavors to advance our understanding of the complex interplay between financial literacy, ethical decision-making, and vulnerability to financial exploitation among young adults in Malaysia. By providing actionable recommendations and strategies informed by empirical evidence, the study aims to empower students to make informed choices, cultivate resilience against financial fraud, and contribute to the promotion of a more secure and ethical society.